Propriedades estruturais e optoeletrônicas dos compostos SrSnO3, SrxBa1-xSnO3 e BaSnO3 - Moreira, Edvan (2011)
In this work we present a study for the structural, electronic and optical properties, at ambient conditions of SrSnO3, SrxBa1xSnO3 (x = 0:2; 0:4; 0:6; 0:8) and BaSnO3 crystals, all of them member of perovskite-type earth stannates class, ASnO3. The theoretical model employed was based on the density functional theory (DFT), considering both the local density and the generalized gradient approximations, LDA-CAPZ and GGA-PBE (OPIUM), respectively. For orthorhombic SrSnO3, the electronic band structure, density of states, complex dielectric function, optical absorption, and the infrared and Raman spectra were computed. Calculated lattice parameters are closed to the experimental measurements, and an indirect band gap E(S -> t )=1.97 eV (2.27 eV) was obtained within the GGA (LDA) level of calculation. E ective masses for holes and electrons were estimated, being very anisotropic in comparison with similar results for orthorhombic CaSnO3. The complex dielectric function and the optical absorption of SrSnO3 are sensitive to the plane of polarization of the incident light. The infrared spectrum between 100-600 cm-1 was obtained, with its main peaks being assigned, and a good agreement between experimental and theoretical peaks of the Raman spectrum of orthorhombic SrSnO3 was achieved. For SrxBa1xSnO3 series, their electronic properties were investigated. The cubic Sr0:2Ba0:8SnO3 has an indirect band gap, while tetragonal Sr0:4Ba0:6SnO3, orthorhombic Sr0:6Ba0:4 SnO3 and Sr0:8Ba0:2SnO3 exhibit a direct band gap. The Kohn-Sham minimum electronic band gap oscillates of 2.62 eV (tetragonal Sr0:4Ba0:6SnO3, LDA) to 1.52 eV (orthorhombic Sr0:6Ba0:4Sn O3, LDA). The effective masses for holes and electrons were estimated, being anisotropic in the series. For cubic BaSnO3, the electronic band structure, density of states, dielectric function and optical absorption were calculated, as well as the infrared absorption spectra after computing the vibrational modes of the crystal at q = 0. Dielectric optical permittivities and polarizabilities at w = 0 and w = ﻿∞ were also obtained. An indirect band gap E(R -> T) of 1.01 eV and 0.74 eV was achieved within the LDA-CAPZ and the GGA-PBE, respectively, which is smaller than the experimental data ( ﻿≈ 3.1 eV). Effective masses of holes and electrons were estimated by parabolic tting along di erent directions at the valence band maximum and conduction band minimum, being highly isotropic for electrons and anisotropic for holes, allowing us to suggest that indirect gap cubic BaSnO3 is a semiconductor with potential for optoelectronic applications. The optical properties reveal a degree of isotropy for the crystal with respect to di erent polarization planes of incident light. The infrared spectrum between 100-600 cm-¹ was obtained, with its main peaks being assigned